Collected papers of P.L. Kapitza. - Kapitsa, P. L. (Petr Leonidovich), 1894-1984 (Pergamon Press, 1965)
Collected Papers of P.L. Kapitza brings together the collected papers of Soviet physicist P.L. Kapitza in areas such as the viscosity of liquid helium below the?-point; the Zeeman and Paschen-Back effects in strong magnetic fields; the influence of friction forces on the stability of high-speed rotors; heat transfer in helium II; and the formation of sea waves by the wind. Kapitza's other papers explore heat transfer in a two-dimensional turbulent flow; dynamical stability of a pendulum when its point of suspension vibrates; and the hydrodynamic theory of lubrication in the presence of roll.